Outcome of Open Reduction Alone or with Concomitant Bony Procedures for Developmental Dysplasia of the Hip (DDH) - Kamal Jamil; Rostam Saharuddin; Ahmad Fazly Abd Rasid; Abdul Halim Abd Rashid; Sharaf Ibrahim (MDPI AG, 2022)
Introduction: Developmental dysplasia of the hip (DDH) is commonly managed in a tertiary centre and regularly involves surgical treatment. The aim of this study is to determine the surgical outcome of DDH patient treated with either open reduction alone or combined with bony procedures in our institution. Methods: Medical records of DDH patients treated surgically were reviewed. Patients were divided into two groups: Group A: underwent open reduction (OR) only; and Group B: underwent open reduction with additional bony procedures (ORB), such as pelvic or femoral osteotomy. Modified McKay classification was used to evaluate the clinical outcome, and Severin classification for the radiological outcome. Presence of avascular necrosis and other post-operative complications were recorded. Results: A total of 66 patients (76 hips) were reviewed with the mean age of 11.9 ± 4.8 years. Mean duration of follow up was 8.6 ± 4.7 years (ranged 2 to 23 years). From our sample, 50/66 patients (75.8%) achieved satisfactory clinical outcome, whereas 48/66 patients (72.7%) had satisfactory radiological outcome. A higher proportion of patients achieved satisfactory outcomes in the OR group compared to the ORB group (p < 0.05), but no difference was seen in terms of radiological outcome (p = 0.80). Overall, 23 hips (34.8%) developed radiographic evidence of avascular necrosis (AVN). Nineteen hips had undergone ORB, although they were mainly (63.2%) Grade I AVN. Incidence of AVN was comparable in both groups (p = 0.63), but presence of AVN led to a higher proportion of unsatisfactory clinical and radiological outcome (p < 0.05). Other complications included redislocation/subluxation (13.6%) and bleeding (0.1%). Conclusions: Good overall outcome of DDH surgery was achieved in our centre. The OR group may produce a better clinical outcome, but with similar radiological results and AVN rate with the ORB group. The presence of AVN is associated with unsatisfactory clinical and radiological outcomes.